AKREDITASI : PENERAPAN BUDAYA MUTU PENDIDIKAN SATUAN PAUD PADA MASA PANDEMI COVID-19 - Muhammad Arif Budiman Sucipto; Syamsul Anwar; R Samidi (Universitas Islam Lamongan, 2021)
Coronavirus Disease 2019 (Covid19) virus has changed the normal order of life in all aspects of life especially the field of education. The epidemic is expected to not interfere with the quality culture of the education unit given the function of education that should provide continuous public service to improve the quality culture of the education unit's performance. The application of quality cultures to the education unit is closely related to the national standards of accreditation process. The goal of research described how a culture of accreditation quality was adopted during the covid pandemic of 19 in the town of tegal. The study Kindergarten is a qualitative approach with a holistic naturalistic descriptive method. Research subjects number 3 advanced education units in the town of tegal. Based on the results of the study, it is expected that the implementation of a culture of accreditation in 3 supedes' education unit has been successful in implementing a quality culture through a national standard of accreditation established by the completion of a document of 8 liabilities, a process standard, a process standard, a standardized education, a management standard, a standard of financing, a standard of education assessment.